Pengaruh Efektivitas Kerja Terhadap Kinerja Pelayanan Pada Badan Keuangan Dan Aset Daerah Kabupaten Gorontalo - Duhe, Sri Herlina; Tahir, Arifin; Aneta, Yanti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out how much influence work effectiveness has on service performance at the Regional Financial and Asset Agency of Gorontalo Regency. The research method used in this research is a quantitative method. Data collection techniques were obtained from the results of a questionnaire with a sample size of 40 respondents. The data analysis technique uses the R2 coefficient of determination test. Based on the results of research that has been conducted, work effectiveness has an influence of 48.2% on service performance at the Gorontalo Regency Regional Financial and Asset Agency, while the remaining 51.8% is explained by other variables not examined in this research, namely time, supervision and motivation .